2014
DOI: 10.1159/000362689
|View full text |Cite
|
Sign up to set email alerts
|

β-Caryophyllene Ameliorates the Alzheimer-Like Phenotype in APP/PS1 Mice through CB2 Receptor Activation and the PPARγ Pathway

Abstract: Background/Aims: The activation of cannabinoid receptor 2 (CB2) has the beneficial effect of reducing neuroinflammatory response in the treatment of Alzheimer's disease (AD) and is suggested to trigger the peroxisome proliferator-activated receptor-γ (PPARγ) pathway; agonists of both receptors improve AD. Recently, the plant metabolite β-caryophyllene was shown to selectively bind to CB2 receptor and act as a full agonist. Methods: In this study, we examined the anti-inflammatory effect of β-caryophyllene in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 73 publications
2
72
0
Order By: Relevance
“…Neuroprotective effects of BCP have been reported in both AD and PD animal models. Oral treatment with BCP prevented AD-like phenotype such as cognitive impairment and activation of inflammation through CB2 receptor activation and the PPARγ pathway (105). As described above, BCP administration also exerts neuroprotective effects in rotenone-challenged rat model of PD by reducing neuroinflammation (44).…”
Section: Terpenes and Neuronal Healthmentioning
confidence: 99%
“…Neuroprotective effects of BCP have been reported in both AD and PD animal models. Oral treatment with BCP prevented AD-like phenotype such as cognitive impairment and activation of inflammation through CB2 receptor activation and the PPARγ pathway (105). As described above, BCP administration also exerts neuroprotective effects in rotenone-challenged rat model of PD by reducing neuroinflammation (44).…”
Section: Terpenes and Neuronal Healthmentioning
confidence: 99%
“…[13][14][15][16] Within this spectrum of diseases, intervention in neurodegenerative disorders using CB2 agonists and inverse agonists is arguably one of the most exciting developments in the cannabinoid field. Specifically, microglia, the resident immune and inflammatory mediators in the central nervous system (CNS), express CB2 in Alzheimer's 17,18 and Parkinson's disease 19 and amyotrophic lateral sclerosis. 6,20 The CB2 is also up-regulated during microglial migration, bacterial insult, and in response to CNS trauma.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] The apparent selective up-regulation of CB2 on microglia in response to insult indicates that CB2 ligands would provide selective effects in only the damaged CNS tissue. In fact, both agonists and inverse agonists of CB2 have been evaluated for efficacy in ameliorating disease progression in in vivo models of traumatic brain injury, 24,25 Alzheimer's 17,18,[26][27][28][29][30] and Parkinson's disease, 19,31,32 amyotrophic lateral sclerosis, 6,20 and multiple sclerosis. 5,[33][34][35][36][37][38][39] The comparable efficacy of agonists and inverse agonists highlights one of the major unanswered questions in this field, what is the optimum functional activity of CB2 ligands?…”
Section: Introductionmentioning
confidence: 99%
“…BCP generates neuroprotective effects against ischemic diseases and AD models (Choi et al, 2013; Cheng et al, 2014) through its anti-inflammation, anti-apoptosis, antioxidation effects, as well as the activation of CB2. However, studies on the effects of BCP on VD are few.…”
Section: Discussionmentioning
confidence: 99%
“…BCP can effectively prevent Alzheimer's disease (AD) (Cheng et al, 2014). Some studies revealed that BCP exerts a prominent protective effect on cerebral neurons (Assis et al, 2014) and thus might be beneficial in the prevention and treatment of cerebral diseases (Guo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%